Revision of the spider genus Sparianthis Simon, 1880 (Araneae, Sparassidae, Sparianthinae) - Rheims, Cristina A. (Zootaxa, 2020)
The genus Sparianthis Simon is revised. Pseudosparianthis Simon and Sampaiosia Mello-Leitão are considered junior synonyms of Sparianthis and thus, seven new combinations are proposed: S. accentuata (Caporiacco) comb. nov., S. chickeringi (Gerstch) comb. nov., S. fusca (Simon) comb. nov., S. megalopalpa (Caporiacco) comb. nov., S. picta (Simon) comb. nov. and S. ravida (Simon) comb. nov. are transferred from Pseudosparianthis and S. crulsi (Mello-Leitão) comb. nov. from Sampaiosia. Two additional new combinations are proposed: Decaphora ambigua (Caporiacco) comb. nov. and Uaiuara jayuyae (Petrunkevitch) comb. nov. are transferred from Pseudosparianthis and, together with S. fusca, are considered nomina dubia. Sparianthis accentuata is considered incertae sedis. The male of S. chickeringi and the female of S. crulsi are described for the first time and six new species are described: S. beebei sp. nov. (♂♀) from Trinidad and S. caracarai sp. nov. (♂♀) from Roraima, S. boraris sp. nov. (♂♀) and S. juruti sp. nov. (♂♀) from Pará, and S. humaita sp. nov. (♂♀) and S. juazeiro sp. nov. (♀) from Acre, all in Brazil. All species are redescribed and illustrated. In addition, an identification key and updated distribution maps for all species of the genus are included.